Pan-cancer multi-omic model of LINE-1 activity reveals locus heterogeneity of retrotransposition efficiency - Solovyov, Alexander; Behr, Julie M.; Hoyos, David; Banks, Eric; Drong, Alexander W.; Thornlow, Bryan; Zhong, Jimmy Z.; Garcia-Rivera, Enrique; McKerrow, Wilson; Chu, Chong; Arisdakessian, Cedric; Zaller, Dennis M.; et al. (Nature communications, 2025)
Somatic mobilization of LINE-1 (L1) has been implicated in cancer etiology. We analyzed a recent TCGA data release comprised of nearly 5000 pan-cancer paired tumor-normal whole-genome sequencing (WGS) samples and ~9000 tumor RNA samples. We developed TotalReCall an improved algorithm and pipeline for detection of L1 retrotransposition (RT), finding high correlation between L1 expression and “RT burden” per sample. Furthermore, we mathematically model the dual regulatory roles of p53, where mutations in TP53 disrupt regulation of both L1 expression and retrotransposition. We found those with Li-Fraumeni Syndrome (LFS) heritable TP53 pathogenic and likely pathogenic variants bear similarly high L1 activity compared to matched cancers from patients without LFS, suggesting this population be considered in attempts to target L1 therapeutically. Due to improved sensitivity, we detect over 10 genes beyond TP53 whose mutations correlate with L1, including ATRX , suggesting other, potentially targetable, mechanisms underlying L1 regulation in cancer remain to be discovered. LINE-1 activity was quantified in a large, pan-cancer dataset, finding locus-specific heterogeneity and new associations using a computational pipeline. A mathematical mediation model of p53 and L1 interactions was inferred. Somatic retrotransposition was seen in Li-Fraumeni Syndrome with heritable TP53 mutations.